What Factors Influence Entrepreneurship? Evidence from Urban Malawi - Matuntha, Steve; Banda, Fredrick Mangwaya (International Review of Management and Marketing, 2025)
This study analyzes the determinants of entrepreneurship in Malawi using Lilongwe city as a case study. The specific objectives of the study were three-fold: To find economic factors that influence entrepreneurship in Lilongwe City, to analyze the social factors that affect entrepreneurship in Lilongwe City, and to examine the demographic factors that influence entrepreneurship in Lilongwe City. The study used secondary data collected from Malawi’s Small Enterprises Development Institute. The results indicate that the attainment of education is negatively associated with entrepreneurship implying that an increase in the number of years of schooling reduces an individual’s willingness to undertake entrepreneurship. Additionally, the study has found that there is a statistically significant positive relationship between age of a respondent and the respondent’s entrepreneurial intentions. Lastly, the study has found that being male is positively related with entrepreneurship thereby suggesting that males are more likely to venture in entrepreneurship than females. Therefore, policy implications arising from the study are two-fold: Firstly, there is need to ensure that entrepreneurial interventions such as trainings are targeted at the 15-64 age group which is an economically active age group. Secondly, there is need to ensure that females are socialized, at a very tender age, to become risk-tolerant as opposed to being risk-averse.